KAJIAN KERAGAAN PASAR DAN DAYA SAING KOMODITAS TEMBAKAU SEBAGAI DAMPAK PERUBAHAN IKLIM DI KABUPATEN GROBOGAN - ENDANG SITI RAHAYU; HERU IRIANTO (Universitas Sebelas Maret, 2013)
This research aim to know performance of market and competitivenessof commodity tobacco as impact alteration of climate in Grobogan Sub-Province. Research is performed with survey method, which is performed to tobacco farmer andmarketer of tobacco. Location was determined by sampling stage from district level and countryside at area sentra production tobacco that is Tanggungharjo District, Tegowanu, Purwodadi and Toroh, at each of district is taken by random 2 country side and is taken by respondent farmer 30 at each of countryside at simple randomsampling, so that the total respondent 120 farmer.